SDG1 - no poverty : making the dream a reality - Cichos, Katarzyna; Salvia, Amanda Lange (Concise guides to the United Nations Sustainable Development Goals., 2019)
This work provides a new look at global problems of poverty and presents applicable solutions to show that the global community can eliminate poverty today and achieve its global promise - Sustainable Development Goal 1 (SDG 1).